PENGARUH TINDAKAN RESTRAIN FISIK DENGAN MANSET TERHADAP PENURUNAN PERILAKU KEKERASAN PADA PASIEN SKIZOFRENIA DI RUANG RAWAT INTENSIF BIMA RUMAH SAKIT JIWA GRHASIA DAERAH ISTIMEWA YOGYAKARTA - Saseno Saseno; Pramono Giri Kriswoyo (JURNAL KEPERAWATAN MERSI, 2013)
Schizophrenia is a hard mental illness and influence the way of think, mood, emotion and behavior, especially to the violent behavior. Violent behavior is a condition when someone is doing something physically dangerous to him/herself, other or to the environment. It happenned becouse of not constuctive anger management. Physical restrain with cuff application is the more effective way to decrease violent patient. The goals of this research is analyzing the influence of physical restrain application to decreasing violant behavior of the schizophrenia patient at intensive room Bima of Grhasia’s Hospital. Research design of this reaserch is a quasy experiment, a pre and post test group design without control group. The place of this research is at intensive room Bima of Grhasia’s Hospital. Samples of this research are 38 respondens taken from Bima room with the purporsive method. The data taken from 2013 Januari until Februari. The instrument is using the decrease violent behavior with RUFA scale observation sheet and analyzing with wilcoxon test Wilcoxon test shown z value -5,386 and p value : 0,000. It shown Ha is adejected, It means violant behavior of the schizophrenia patient is different. There is decreasing of the violent behavior after physical restrain with cuff application Physical restrain with cuff application influenced to the decrease violent behavior of schizophrenia patient at intensive room Bima of Grhasia’s Hospital